2012
DOI: 10.3758/s13421-011-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory–motor learning influences auditory memory for music

Abstract: In two experiments, we investigated how auditorymotor learning influences performers' memory for music. Skilled pianists learned novel melodies in four conditions: auditory only (listening), motor only (performing without sound), strongly coupled auditory-motor (normal performance), and weakly coupled auditory-motor (performing along with auditory recordings). Pianists' recognition of the learned melodies was better following auditory-only or auditory-motor (weakly coupled and strongly coupled) learning than f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
61
2
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 35 publications
10
61
2
5
Order By: Relevance
“…The difference in N2 amplitudes between the tapping positive and the listening positive conditions could be explained by 'the production effect' (MacLeod et al, 2010). For example, it has been shown that musical melodies played by the subject with normal auditory feedback are better recognized (which was associated with enhanced N2) compared to melodies that were only heard by the subject and not actively produced by them (Brown & Palmer, 2012;Mathias et al, 2015). Thus, this enhanced N2 will in turn lead to stronger memory retention.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in N2 amplitudes between the tapping positive and the listening positive conditions could be explained by 'the production effect' (MacLeod et al, 2010). For example, it has been shown that musical melodies played by the subject with normal auditory feedback are better recognized (which was associated with enhanced N2) compared to melodies that were only heard by the subject and not actively produced by them (Brown & Palmer, 2012;Mathias et al, 2015). Thus, this enhanced N2 will in turn lead to stronger memory retention.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, it is as though the vocal tract "remembers" the exact tension associated with each pitch in the representation. However, this possibility remains mostly theoretical, as little evidence of such procedural memory has been presented in the vocal domain thus far(see, e.g., Brown & Palmer, 2012). Also, as Levitin (2013) has recently noted, procedural memory cannot solely account for the accurate pitch reproduction that adults are capable of.…”
Section: Song Memorymentioning
confidence: 98%
“…Findings within the visual domain suggest that the ''mere observation of movements leads to the formation of a lasting specific memory trace in movement representations that resembled that elicited by physical training'' (Stefan et al, 2005, p. 9344). It is also well known that auditory-motor associations acquired while learning to play a piece can be determinant for later auditory recognition (Brown & Palmer, 2012). However, most of the relevant literature focuses on a population of well-trained musicians engaged in expertise-related tasks with their own instrument.…”
mentioning
confidence: 99%